Faktor Eksternal Penyebab Kesulitan Belajar Mahasiswa pada Mata Kuliah Mekanika Teknik I - Aziz Santoso; M. Agphin Ramadhan; Arris Maulana (Universitas Negeri Padang, 2020)
This research aims to describe the external factors of the learning difficulties of building technical education students on the course of mechanical mechanics 1 at the State University of Jakarta. This research uses the ex-post facto method with a quantitative approach. This research is done by collecting data from questionnaires, interviews, and learning outcomes. Based on the results of the study, the causative factors of students' learning difficulties in the course of Mechanical Mechanics 1 in the Building Engineering Education study program are factors of means and infrastructure, factors of learning methods and factors of campus interaction. On the factors of facilities and infrastructure, 39.8% of respondents agreed that the absence of Mechanical Mechanics module 1 made them difficult to learn, 34.9% of respondents agreed that the room was too full by students making it unable to focus on learning Mechanical Mechanics 1, and 33.7% of respondents strongly agreed that they were uncomfortable studying Mechanical Mechanics 1 in the classroom when there was noise of motors, cars or other transportation from the outdoors. On the learning method factor, 55.4% of respondents disagreed they had studied Mechanical Mechanics 1 material at night for tomorrow's material. On the campus interaction factor, 56.6% of respondents disagreed they were close to the lecturer.